The methods and skills of history : a practical guide - Salevouris, Michael J.; Furay, Conal (Chichester, West Sussex U.K. : Wiley-Blackwell, 2015)
"Widely acclaimed for its accessibility and engaging approach to the subject, the fourth edition of The Methods and Skills of History combines theory and instruction with hands-on practice, making it a comprehensive guide to historical research and writing. Combines theory with hands-on practice in its introduction to historical methods. Includes a series of field-tested exercises designed to make the research and writing of history more meaningful and accessible to readers. Features expanded coverage of writing history and up-to-date coverage of online research. Designed to strengthen students' critical thinking and communication skills"--Provided by publisher.
Part I: Historical thinking -- Part II: Confronting the historical account -- Part III: Doing History -- Part IV: Historiography.
"Includes a series of field-tested exercises designed to make the research and writing of history more meaningful and accessible to readers"--Provided by publisher.
Includes bibliographical references (p. 301-306) and index.
Keywords: History -- Examinations, questions, etc; History -- Methodology